ASSESSMENT OF QUALITY OF LIFE POST CARDIAC DEVICE IMPLANTATION: AN AFIC EXPERIENCE - Parveen, Sajida; Asad, Muhammad; Sultana, Sumera; Khan, Aleena; Hayat, Azmat; Kousar, Azra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess quality of life (QOL) after cardiac device implantation using WHO validated questionnaire. Study Design: Descriptive cross sectional study. Place and Duration of Study: Study was conducted at Electrophysiology department of AFIC/NIHD Rawalpindi from June 2021 to Sep 2021 Methodology: A total of 135 patients of both genders were evaluated regarding QOL. The evaluation included data related to physical, personal, psychological and social domains using WHO based quality of life questionnaire. Statistical analysis was conducted using SPSS-24. Mean and standard deviation was calculated for continuous variables while frequency and percentages for categorical variables. Results: Out of 135 patients, 102 (75.6%) were men and 33 (24.4%) were women with the mean age of 67.09 ± 8.80 years. Eight-two (60.7%) of the patients rated their overall quality of life as good post implantation. In domains related to physical, psychological, social and environment majority of patients were neither satisfied nor dissatisfied. Questions related to health satisfaction and peer support showed more positive responses. Conclusion: Overall QoL of patients was good after device implantation. Majority of the respondents were neutral about the queries related to physical, psychological, social domains. However, in terms of physical health most of the patients reported it to have been improved.